Resistance, hegemony, and politics in sports: Sports policy issues in Japan around the 2009 regime change - Mizukami, H. (Japan Journal of Physical Education, Health and Sport Sciences, 2023)
This study identifies a period around the change of government in 2009 (Heisei 21) as a major milestone in Japanese political and sports history. Japanese sports policy during this period did not necessarily support the promotion of community sports clubs (CSC). On the contrary, the abolition of such sports club projects was an issue at the time. NPOs offering intermediary support for community sports clubs encouraged the practice of "resistance" against this trend in an attempt to seek "hegemony." They also advocated "political engagement" with the goal of participation in policy making.